On the Abnormally Strong Westward Phase of the Mesospheric Semiannual Oscillation at Low Latitudes During March Equinox 2023 - Suclupe, Jose (2024)
Different meteor radars at low latitudes observed abnormally strong westward mesospheric winds around the March Equinox of 2023, that is, during the first phase of the Mesospheric Semiannual Oscillation. This event was the strongest of at least the last decade (2014–2023). The westward winds reached −80 m/s at 82 km of altitude in late March, and decreased with increasing altitude and latitude. A considerable increase in the diurnal tide amplitude was also observed. The Whole Atmosphere Community Climate Model with thermosphere-ionosphere eXtension constrained to meteorological reanalysis up to ∼50 km does not capture the observed low-latitude behavior. Additionally, these strong mesospheric winds developed during the westerly phase of the Quasi-Biennial Oscillation, in accordance with the filtering mechanism of gravity waves in the stratosphere proposed in previous works. Finally, analysis of SABER temperatures strongly suggests that the breaking of the migrating diurnal tide may be the main driver of these strong winds.